Evaluation and comparison of castability between an indigenous and imported Ni-Cr alloy - Ganesh Ramesh; T V Padmanabhan; Padma Ariga; R Subramanian (Wolters Kluwer Medknow Publications, 2011)
Context: Since 1907 casting restorations have been in use in dentistry. Numerous companies have been manufacturing and marketing base metal alloys. Gold was a major component of casting alloys. But alloys with less than 65% gold tarnished easily and the increase in cost of gold post-1970s lead to the revival of base metal alloys such as nickel-chromium and cobalt-chromium alloys which were in use since 1930s. Aim: This study was conducted to evaluate and compare the castability between an indigenous alloy and an imported alloy, as imported base metal alloys are considered to be expensive for fabrication of crowns and bridges. Materials and Methods: This study was conducted to evaluate and compare the castability (for the accurate fabrication of crowns and bridges) between an indigenous base metal alloy-Non-ferrous Materials Technology Development Centre (NFTDC), Hyderabad (Alloy A) -and an imported base metal alloys (Alloy B). Castability measurement was obtained by counting the number of completely formed line segments surrounding the 81 squares in the pattern and later calculating the percentage values. The percentage obtained was taken as the castability value for a particular base metal alloy. The percentage of castability was determined by counting only the number of completely cast segments in a perfect casting (81 × 2 = 162), and then multiplying the resulting fraction by 100 to give the percentage completeness. Statistical Analysis Used: The Student t-test was used. Results: When the castability of alloys A and B was compared, the calculated value was less than the tabular value (1.171 < 2.048) leading to the conclusion that castability between alloys A and B is insignificant. Therefore we conclude that both the alloys have the same castability. Conclusions: Using the above-mentioned materials and following the method to test castability, we were able to derive favorable results. As the results were satisfactory, we can conclude that the castability of the indigenous alloy is on par with the imported alloy.